(untitled) (Amsterdam, 2009)
This volume is divided into three sections. The articles in the first section ex-plore the theoretical underpinnings of assessing translation and interpreting, spe-cifically as they relate to construct definition and rubric development. The articles in the second section discuss results of empirical research implementing quasi experimental and non-experimental designs. These studies delve into evaluation methods, including holistic/intuitive-impressionistic and analytical and dichoto-mous items-methods, and the application of evaluation scales to grading. They also provide insight into types of assessment (e.g. meaning-oriented) and assessment constructs (e.g. cohesion). The articles in the third section present case studies that are of a broader scope, describing admissions tests and professional certification.
Keywords: Biên dịch và phiên dịch,Translating and interpreting; Đánh giá,Evaluation